Observational study on clinicopathological profile of thrombocytopenia cases in a medical college hospital - Kumar, Ajay; Priyadarshi, Avinash; Kumar, Sanjay; Kumar Lal, Prabhat (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Thrombocytopenia is a commonly encountered condition with varying aetiologies ranging from infective to chronic conditions and malignancies. Knowledge of causes and pattern of disease is helpful in management of cases. Aims & objectives: The present study was conducted to assess the causes, clinical profile and findings of laboratory investigations of patients suffering from thrombocytopenia. Material & Methods: The present cross-sectional hospital-based study was conducted upon 99 patients suffering from thrombocytopenia. Detailed clinical history, physical examination and reports of laboratory investigations were noted. Results: 34.3% patients belonged to the age group of 21-30 years. 57.6% of them were males. Thrombocytopenia was mild (1,00,000-1,50,000) in 24.2% patients, moderate (50,000-1,00,000) in 52.5% and severe (<50,000) in 23.2%. Dengue accounted for 31.3% cases, malaria for 16.2%, enteric fever for 7.1% and septicaemia for 3%. Megaloblastic anaemia was responsible in 24.2% cases. Most common site for bleeding was skin and mucous membrane where bleeding manifested in the form of petechiae, purpura and ecchymosis (18.2%). Conclusion: Knowledge of causes and pattern of disease is helpful in management of cases.